1999
DOI: 10.1007/s003740050564
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nitrogen on atrazine and 2, 4 dichlorophenoxyacetic acid mineralization in blackwater and redwater forested wetland soils

Abstract: Microcosms were used to determine the influence of N additions on active bacterial and fungal biomass, atrazine and dichlorophenoxyacetic acid (2,4-D) mineralization at 5, 10 and 15 weeks in soils from blackwater and redwater wetland forest ecosystems in the northern Florida Panhandle. Active bacterial and fungal biomass was determined by staining techniques combined with direct microscopy. Atrazine and 2,4-D mineralization were measured radiometrically. Treatments were: soil type, (blackwater or redwater fore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 39 publications
2
8
0
Order By: Relevance
“…To the extent they saw soil microbial biomass shifts, interpretation, especially in light of earlier literature, suggests this could be due to N enrichment resulting from the PAM addition rather than a direct effect of the PAM polymer chemistry itself. This has been seen in other studies where high soil N concentration reduced microbial biomass and mineralization of cellulose, lignin, and herbicides (Entry, 1999(Entry, , 2000 PAM IN AGRICULTURE AND ENVIRONMENTAL LAND 127 Entry and Backman, 1995;Entry et al, 1993). Thus if large amounts of PAM are applied to soil, it is reasonable to expect the additional N contained in PAM may slightly reduce microbial biomass.…”
Section: Pam Effect On Organisms In Runoff and Soilsupporting
confidence: 53%
“…To the extent they saw soil microbial biomass shifts, interpretation, especially in light of earlier literature, suggests this could be due to N enrichment resulting from the PAM addition rather than a direct effect of the PAM polymer chemistry itself. This has been seen in other studies where high soil N concentration reduced microbial biomass and mineralization of cellulose, lignin, and herbicides (Entry, 1999(Entry, , 2000 PAM IN AGRICULTURE AND ENVIRONMENTAL LAND 127 Entry and Backman, 1995;Entry et al, 1993). Thus if large amounts of PAM are applied to soil, it is reasonable to expect the additional N contained in PAM may slightly reduce microbial biomass.…”
Section: Pam Effect On Organisms In Runoff and Soilsupporting
confidence: 53%
“…Intracellular and extracellular activity have been noted, and production and secretion of the enzyme appears to be dependent on C availability, as cells cannot derive C directly from PAM. Elevated soil N concentrations have been shown to reduce microbial biomass and mineralization of cellulose, lignin and herbicide (Entry, 1999(Entry, , 2000Entry et al, 1993;Entry and Backman, 1995). When large amounts of PAM are applied to soil, additional N contained in PAM may reduce microbial biomass.…”
Section: Discussionmentioning
confidence: 99%
“…3a and b), and CH 4 production competed for electrons with HCB dechlorination. Secondly, it has been reported that excessive N addition could alter enzymatic systems of soil responsible for the degradation [12,13], and inhibit specific degraders' ability [14]. The application of NO 3 − -N decreased PeCB production rates significantly (Fig.…”
Section: Dechlorinated Metabolitesmentioning
confidence: 96%
“…Some studies confirmed that N addition accelerated the degradation of organic contaminants owing to stimulating microbial activity [9][10][11]. Some studies showed that N addition inhibited the degradation of organic pollutants, because N sources could alter enzymatic systems responsible for the degradation and inhibit specific degrader's ability [12][13][14]. In addition, some other studies suggested an optimal C/N ratio for POPs biodegradation, and N sources were commonly added when carbon sources were excessive in the environment [15][16][17].…”
Section: Introductionmentioning
confidence: 97%